Residents' perceptions toward tourism development: A factor-cluster approach - Sinclair-Maragh, G.; Gursoy, Dogan; Vieregge, M. (Elsevier BV, 2015)
The purpose of this study is to classify residents into separate groups based on their perceptions of the impacts of tourism development on their community as they relate to economic, social, cultural, environmental, and public service factors, and to identify similarities and differences among these groups. Using data collected from residents of two communities that are new to tourism development, a factor-cluster approach was utilized to identify four groups of residents. The "public service and environment focused group" was mostly concerned with the availability of amenities, facilities, and environmental issues; the "community focused group" was generally concerned with the social and cultural impacts; the "community-public service and environment focused group" comprised those individuals who considered both sets of issues; and the "inconsequential group" included individuals who did not have any specific concerns about the impacts of tourism development. A descriptive profile of each group and the significant differences among groups are provided. Based on the findings, implications for developers and policy makers are discussed.